Conventional Pig as Animal Model for Human Renal Drug Excretion Processes: Unravelling the Porcine Renal Function by Use of a Cocktail of Exogenous Markers - Dhondt, Laura; Croubels, Siska; De Paepe, Peter; Wallis, Steven C.; Pandey, Saurabh; Roberts, Jason A.; Lipman, Jeffrey; De Cock, Pieter; Devreese, Mathias (Frontiers in Pharmacology, 2020)
Over recent years, pigs have been promoted as potential animal model due to their anatomical and physiological similarities with humans. However, information about the contribution of distinct renal elimination processes (glomerular filtration rate (GFR), effective renal plasma flow (ERPF), tubular secretion and reabsorption) in pigs is currently limited. Therefore, a cocktail of renal markers, consisting of iohexol (GFR), para-aminohippuric acid (ERPF and net tubular anion secretion), pindolol (net tubular cation secretion) and fluconazole (net tubular reabsorption) were administered intravenously to 7-week-old male conventional pigs. Plasma and urinary concentrations were determined using validated analytical methods. The clearance of iohexol (GFR) was 97.87 ± 16.05 mL/min/m² (mean ± SD). The ERPF, calculated as the renal clearance of PAH, was 226.77 ± 62.45 mL/min/m², whereas the net tubular secretion of PAH was 130.28 ± 52.62 mL/min/m². The net tubular secretion of R-pindolol and S-pindolol was 13.53 ± 12.97 and 18.01 ± 39.23 mL/min/m², respectively. The net tubular absorption of fluconazole was 78.32 ± 13.52 mL/min/m². Overall, this cocktail of renal markers was considered to be safe for use in pigs, since no adverse effects were observed. Iohexol, PAH and fluconazole were considered suitable renal marker to assess the porcine renal function. Pindolol seems less appropriate due to the high degree of non-renal clearance in pigs. The values of GFR, ERPF, and anion secretion are within the same range for both human and pig. Regarding the tubular reabsorption of fluconazole, slightly higher values were obtained for pigs. Nevertheless, these results indicate the conventional pig could be an appropriate animal model to study renal drug elimination processes in humans.